2012
DOI: 10.2463/mrms.11.75
|View full text |Cite
|
Sign up to set email alerts
|

CT versus MR Imaging of Hepatocellular Carcinoma: Toward Improved Treatment Decisions

Abstract: Detection, characterization, staging, and treatment monitoring are major roles of diagnostic imaging of liver cancers. Developments in multidetector-row computed tomography (MDCT) technology have increased the spatial and temporal resolution of CT to allow more precise evaluation of the hemodynamics of liver tumors and improve the diagnostic accuracy of dynamic MDCT. The high spatial and temporal resolutions of dynamic MDCT enable us to reconstruct 3-dimensional (3D) images that are very useful for pretreatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…However, perfusionbased HCC-characteristics are not always present in early HCC and differentiation from dysplastic nodules and even regenerative nodules can be challenging [5,8]. Different other imaging techniques, in particular MRI using sequence-dependent signal characteristics, dynamic contrast agent studies and hepatospecific contrast agents have been therefore recommended for a more confident diagnostic [9][10][11]. Admitting that increasing arterialization is a characteristic of HCC, non-invasive quantification of the tumor arterial supply could represent surrogate information expected to deliver essential information even in less well A c c e p t e d M a n u s c r i p t tissue generating time density curves (TDC) [12,13].…”
Section: Introductionmentioning
confidence: 98%
“…However, perfusionbased HCC-characteristics are not always present in early HCC and differentiation from dysplastic nodules and even regenerative nodules can be challenging [5,8]. Different other imaging techniques, in particular MRI using sequence-dependent signal characteristics, dynamic contrast agent studies and hepatospecific contrast agents have been therefore recommended for a more confident diagnostic [9][10][11]. Admitting that increasing arterialization is a characteristic of HCC, non-invasive quantification of the tumor arterial supply could represent surrogate information expected to deliver essential information even in less well A c c e p t e d M a n u s c r i p t tissue generating time density curves (TDC) [12,13].…”
Section: Introductionmentioning
confidence: 98%
“…64,65 Several studies have shown that gadoxetic acid-enhanced MR imaging is useful in diagnosing conventional HCCs and, in fact, may sometimes be more reliable than dynamic contrast-enhanced 16-to 64-slice multidetector-row CT for this purpose. 9,36,66,67 When using an extracellular GBCA, sensitivity and specicity of MR imaging are excellent even for small HCCs. 68 However, some researchers suggest that the hepatocyte phase of gadoxetic acid might have added value to detect more HCCs than dynamic phases especially for less-experienced observers.…”
Section: Added Value For Hepatocellular Carcinoma (Hcc) Improving Diamentioning
confidence: 99%
“…It has actually become common to encounter cases where hypervascular HCC or nodule-in-nodule HCC that is undetectable by MDCT is detected in a routine screening by EOB-MRI because of early enhancement in the arterial phase or clear hypointensity in the hepatobiliary phase [11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103]. Furthermore, studies comparing the diagnostic performance of EOB-MRI and MDCT for hypervascular HCC have shown that EOB-MRI is superior or, at the very l...…”
Section: Diagnostic Algorithmmentioning
confidence: 99%